Therapeutic Relationship and Dropout in High-Risk Adolescents’ Intensive Group Psychotherapeutic Programme - Hauber, Kirsten; Boon, Albert; Vermeiren, Robert (Frontiers in Psychology, 2020)
Objective: Dropout rates in youth psychotherapy are high. An important determinant of dropout is the quality of the therapeutic relationship. This study evaluated the association between the therapeutic relationship and dropout in an intensive mentalization based treatment (MBT) for adolescents with personality disorders. Method: Patients (N = 105) included were dropouts (N = 36) or completers (N = 69) of intensive MBT treatment. The therapeutic relationship was measured with the Child version of the Session Rating Scale (C-SRS) that was completed after each group therapy session by the patient. For each patient, the treatment termination status (dropout or completer) was indicated by the treatment staff. The reliable change index (RCI) was calculated for the C-SRS to determine significant changes in the therapeutic relationship. Results: Both groups started with similar scores on the C-SRS, while at the end of the treatment period the scores differed significantly between dropouts and completers. On average, the scores of completers increased from the start to the end of therapy while the scores of dropouts decreased during therapy, although dropout could not be predicted based on the C-SRS scores. During the last two sessions however a significant decrease (RCI) in C-SRS scores occurred more often for dropouts. Conclusions: Our findings show that the patient’s judgement of the quality of the therapeutic relationship should be monitored continuously, and decreases discussed with the patient and the group, with the aim to prevent dropout.